Pengaruh Sistem Absensi Digital dan Pemantauan Produktivitas Terhadap Kinerja Karyawan Perusahaan PT. Sumber Alfaria Trijaya - Muh Yani; Altri Wahida; Saharuddin Saharuddin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study analyzes the effect of digital attendance systems and productivity monitoring on employee performance at PT Sumber Alfaria Trijaya in North Luwu Regency. Using a quantitative descriptive approach and through Slovin equation to 180 employees selected 65 respondents from those. Data were collected using questionnaires and analyzed through validity, reliability, multiple linear regression, t-test, and F-test with IBM SPSS Statistics 26. The results show that both the digital attendance system and productivity monitoring hold significant effect on employee performance. Simultaneously, both variables also significantly influence on employee performance. These findings indicate that digital systems in attendance and productivity management enhance discipline, efficiency, and accountability. Therefore, companies should strengthen digital integration in human resource management to improve performance and competitiveness in the modern retail sector.